The properties of metal contacts on TiO2 thin films produced by reactive magnetron sputtering - Brus V. V.; Kovaluk Z. D.; Maryanchuk P. D.; Orletsky I. G.; Maystruk E. V. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2010)
The article deals with research on volt-ampere characteristics of metal contacts (Al, Cr, In, Mo, Ti) on titanium dioxide thin films and influence of annealing in vacuum on their electric properties. Volt-ampere characteristics measurements were taken by three-probe method. There was established that indium contact on TiO2 thin films possessed sharply defined ohmic properties.